A cross-sectional study to evaluate malnutrition prevalence in under 5 children and health seeking behaviour of their parents in an urban slum area of a metropolitan city - Inkane, Swapnil M.; Chavan, Sushant S.; Bawa, Mukesh S.; Kinge, Amol D. (International Journal Of Community Medicine And Public Health, 2019)
Background: Malnutrition is widespread in rural, tribal and urban slum areas and it is a significant public health problem described as a silent killer, silent emergency, and invisible enemy affecting those who cannot express their voice and have to depend upon others for their advocacy. Numerous studies showed that education of parent’s, especially maternal education emerges as a key element of an overall strategy to address malnutrition. The best global indicator of children’s wellbeing is growth. Assessment of anthropometry is the single measurement that best defines the nutritional and health status of children, and provides an indirect measurement of the quality of life of the entire population. Methods: Community based cross-sectional study was carried out in an urban slum area of Mumbai city, Maharashtra. Total 300 children of 0-5 years of age were enrolled in the study. A list of all the children below five years of age belonging to study area was taken from the health post situated in premises of UHTC. All mothers or primary care takers of the children were interviewed and weight and height of the children was recorded. Results: Prevalence of underweight, stunting and wasting was 69.33%, 60.33% and 45.66% respectively. Mother’s literacy, low birth weight and morbidities like diarrhoea, fever and cough in previous fifteen days were significantly associated with malnutrition. Conclusions:Chronic malnutrition was more prevalent in this area. Mother’s literacy had a much higher impact on better nutritional status of children. Morbidities like diarrhoea, fever and cough had made the children nutritionally vulnerable as malnutrition was higher in those children.